Tafsir Kontekstual Terhadap Ayat Tentang Larangan Menjadikan Non-Muslim Sebagai Pemimpin: Studi Terhadap Surat Al-Maidah Ayat 51 - Matswah, Akrimi - (Lajnah Pentashihan Mushaf Al-Qur'an, 2016)
The discussion over the non-Muslim leadership in Indonesia is often referred which textually indicate prohibition of choosing or appointing non-Muslim asÃ‚Â leader in the contitutional state. Among the verses is Q.S. al-Maidah: 51. The majority of commentators understood this verse as a form of a prohibition on non-Muslim leadership. Therefore It became a guide in choosing a leader, where religion becomes the primary assessment, not the capacity and capabilities, as well as commitment and responsibility. Therefore It is important to build the societies paradigm related to the non-Muslim relationships in the government. Such efforts can be done by reviewing the paragraph regarding the prohibition to make non-Muslim as a leader, as in the Q.S al-Maidah 51 by applying a contextual interpretation method initiated by Abdullah Saeed. It is an attempt to explore the context of the verse and discover new meanings that are relevant to the current context.Keyword: Contextual approach, muslim-christian relationship